Knowledge, Practice and Use of Pesticides among Commercial Vegetable Growers of Dhading District, Nepal - Shrestha, P.; Koirala, P.; Tamrakar, A. S. (Journal of Agriculture and Environment, 2010)
A field study was conducted to evaluate knowledge, practice and use of pesticides among thirty commercial vegetable growers of Dhading district of Nepal. More than four in five were using pesticides and more than one third were using it for more than six years. Nearly half of them spray pesticides five to six times. More than one-sixth pesticides used were extremely hazardous, which were barred for general agriculture use. Waiting period is less than four days for nearly two-third growers. More than three-forth know the adverse effect of pesticides and nearly half experienced symptoms of health hazards. Majority did not receive any official training on pesticides and nearly one-third doesn't read information available in pesticide label. Nearly half were not using Personal Protective Equipment during pesticide application. Nearly two-third throw pesticide container anywhere after using it. The finding of this study is oriented to the following recommendation: the need for awareness, education and training on the uses of pesticides to the farmers and effective monitoring program for pesticide residues in vegetables. Key words: Awareness; Health effects; IPM; Pesticides; Vegetables The Journal of AGRICULTURE AND ENVIRONMENT Vol. 11, 2010 Page: 95-100 Uploaded date: 16 September, 2010